Radio Frequency Identification from System to Applications - Bin Ibne Reaz, Mamun (IntechOpen, 2013)
RFID based application creates tremendous new business opportunities such as the support of independent living of elderly and disabled persons, efficient supply chains, efficient anti-counterfeiting and better environmental monitoring. RFID data management, scalable information systems, business process reengineering, and evaluating investments are emerging as significant technical challenges to applications underpinned by new developments in RFID technology. This book presents the contributions from world leading experts on the latest developments and state-of-the-art results in the RFID field to address these challenges. The book offers a comprehensive and systematic description of technologies, architectures, and methodologies of various efficient, secure, scalable, and reliable RFID and RFID based applications.